Gestão educacional: formação continuada de professores frente à identidade institucional - Lima, Marcos Epifanio Barbosa (Universidade do Vale do Rio dos Sinos, 2018)
The present dissertation aims to address educational management in its correlation with continuing teacher formation and institutional identity. In this sense, in order to mark the study in a way that was understood nationally and officially by the state on these themes, we sought to analyze information from government documents and, especially, the virtual spaces provided by the Ministry of Education regarding its approach and content, offered through teacher training programs and projects. In complementarity to the study on state planning for teacher training, a documentary analysis was carried out on the training of teachers in an educational unit of the Jesuit Education Network, a private, philanthropic and confessional entity. In this research, two approaches was also offered in this empiric space: rescue of the teachers' memory regarding the formation of teachers in the form of a joint narrative and the offer of a pedagogical workshop with managers of the School on the institutional identity of the Unit.
Keywords: Gestão educacional; Formação continuada de professores; Identidade institucional; Educational management; Continuing teacher formation; Institutional identity; ACCNPQ::Ciências Humanas::Educação